Phytotelmata accounts for Aedes breeding places in Mantup Sub-district, Lamongan District, Indonesia - SHIFA FAUZIYAH; SAUDI FITRI SUSANTI; HARIYONO HARIYONO; VERA FAZIRRAH; ANIK EKO NOVITASARI; NUR FADHILAH; TEGUH HARI SUCIPTO; SIN WAR NAW (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fauziyah S, Susanti SF, Hariyono H, Fazirrah V, Novitasari AE, Fadhilah N, Sucipto TH, Naw SW. 2023. Phytotelmata accounts for Aedes breeding places in Mantup Sub-district, Lamongan District, Indonesia. Biodiversitas 24: 4820-4828. Dengue infection still remains a public health problem in Indonesia, which is classified as a tropical country. Some environmental factors that contribute to the transmission of dengue infection are human migration, human activity, food supply, and climate change. The other type of breeding place is natural breeding habitats, called phytotelmata. This study aims to investigate the diversity of Aedes species in phytotelmata from Mantup Sub-district, Lamongan, East Java, Indonesia. The analytical observational study was conducted with a purposive sampling design. Mosquito larvae collection was carried out from February to March 2023 in Mantup Sub-district, an endemic region of dengue infection in Lamongan. Immature mosquitoes were reared in the laboratory till they merged into adult mosquitoes. This study found four groups of phytotelmata: leaf axils, bamboo joints, fallen leaves, and coconut shells. Leaf axils were the predominant type of phytotelmata (86.67%). Meanwhile, the lowest percentage was coconut shells and fallen leaves (3.33%). A total of 56 mosquito larvae consisting of 12 male Aedes aegypti, 21 female Ae. aegypti, 12 male Aedes albopictus, and 11 female Ae. albopictus were collected from 30 observation points. Eleven families of phytotelmata were found in this study. The predominant family was Araceae (33.3%), while the lowest were Agavaceae, Commelinaceae, Marantaceae, and Liliaceae (3.33%). Phytotelmata accounts for mosquito breeding places, which should be noticed and considered in dengue vector control programs.